Normal Walking Speed According to Age and Gender in Preliminary Students in Surabaya - Ananda, Naoval Diza; Laswati, Hening; Rejeki, Purwo Sri; Suyoko, Andri (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: Studies on walking have been developed recently because the speed of walking plays an important role in making predictions related to physical health. However, studies of walking speed in children are still relatively few even though the need for such data is quite high considering that walking speed can be used as a parameter to measure physicalhealth.Aim: The purpose of this study is to know the difference in walking speed based on age and gender in elementary school students.Methods: This study used an analytic observational study with a cross-sectional approach. All samples are students from Mojo VI State Elementary School Surabaya aged 7 to 12 years who meet the inclusion criteria using 10-meter walk test. The variable studied was walking speed. Method of sampling was conducted at Mojo VI State Elementary School Surabaya. Walking speed analysis was carried out by using the Kruskal-Wallis test for walking speed based on age and an unpaired T test for walking speed based on gender.Results: This research included 170 subjects that are 90 males and 80 males. Based on age, seven years old students have anaveragewalkingspeedof(1.30±0.21)m/s, eightyearsold students with(1.23±of0.18)m/s, nine yearsold  students with (1.24 ± 0.17) m/s, ten years old students with (1.24 ± 0.19) m/s. eleven years old students with (1.31 ± 0.22) m/s, and twelve years old students with (1.27 ± 0.20) m/s. Based on gender, the average walking speed obtained in male was (1.26 ± 0.19) m/s, while the average walking speed obtained in female was (1.26 ± 0,20)m/s.Conclusion: There is no difference in the speed of walking based on age (p=0.440) at the age of 7 to 12 years and in both genders (p=0.910).